2015
DOI: 10.18278/epa.1.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing gender equity through evidence‐based policymaking? Theorizing and tracing the use of systematic knowledge in family and tax policy reforms

Abstract: How can evidence—systematically generated substantive knowledge—be used to reach policy outcomes that promote gender equity? Initial hypothetical answers to this question are derived from three distinct theories of the policy process: the Rational Policy Cycle (RPC), the Advocacy Coalition Framework (ACF), and the Multiple Streams Approach (MSA). With the help of these theoretical frameworks, we trace the use of evidence in four case studies in the fields of family and tax policy in Swiss Cantons. These empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
11
0
5
Order By: Relevance
“…The MSF conceives of the policy process as three streams, operating largely independent of each other: problem, policy, and politics. As discussed above, one fruitful understanding of the nature of these streams is that of “discursive channels” (Blatter et al., , p. 12). In the problem stream, all issues and problems that compete for attention in a political system are debated.…”
Section: Knowledge Utilization In the Policy Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The MSF conceives of the policy process as three streams, operating largely independent of each other: problem, policy, and politics. As discussed above, one fruitful understanding of the nature of these streams is that of “discursive channels” (Blatter et al., , p. 12). In the problem stream, all issues and problems that compete for attention in a political system are debated.…”
Section: Knowledge Utilization In the Policy Processmentioning
confidence: 99%
“…But from an argumentative perspective, policy entrepreneurs can only act in the valley created by a discourse to couple the streams (Winkel & Leipold, ). In this creation of a discourse, scientific knowledge and evidence is an important instrument within the MSF to generate attention for problem or policy issues, and for “establishing a connection between a policy measure and a policy issue” (Blatter et al., , p. 13). “Argumentative coupling,” which is developed in the following section, can illuminate how these connections are build.…”
Section: Knowledge Utilization In the Policy Processmentioning
confidence: 99%
See 2 more Smart Citations
“…A further drawback is that not every canton can afford to provide for well-funded and professionalized implementation units (Sager 2003). Moreover, authors have shown the crucial importance of the issue framing and of the use of evidence during the different local policymaking processes, sometimes leading to very distinct cantonal outcomes (Balthasar and Müller 2014;Blatter, Bombach, and Wiprächtiger 2015). The central role of the horizontal cooperation among federated entities for the adoption of fragmented or countrywide policies in federalist countries has also been evidenced (Rothmayr, Varone, and Montpetit 2003).…”
mentioning
confidence: 99%